2011
DOI: 10.4049/jimmunol.1003111
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: NLRC5-Dependent Activation of the Inflammasome

Abstract: The nucleotide-binding domain (NBD) leucine rich repeat (LRR) containing proteins, NLRs, are intracellular sensors of PAMPs and DAMPs. A subgroup of NLRs can form inflammasome complexes, which facilitate the maturation of pro-caspase-1 to caspase-1, leading to IL-1β and IL-18 cleavage and secretion. NLRC5 is predominantly expressed in hematopoetic cells and has not been studied for inflammasome function. RNAi-mediated knockdown of NLRC5 nearly eliminated caspase-1, IL-1β and IL-18 processing in response to bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
185
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(194 citation statements)
references
References 23 publications
6
185
2
1
Order By: Relevance
“…To determine whether NLRC5 is involved in inflammasome activation, NLRC5 or a mutant with the LRR domain deleted, a mutation that is designed to remove the autoinhibitory effect of LRRs, was overexpressed to determine the effect on the processing of procaspase-1 and pro-IL-1β. Overexpressed NLRC5 or its deletion mutant activated this processing, and the mutant also promoted NLRP3 inflammasome activation (Sup- plementary information, Figure S5A), consistent with recent reports [16,17]. Also as reported previously [16], NLRC5 associated with NLRP3 (Supplementary information, Figure S5B), and the NACHT domain of NLRC5 mediated this association with NLRP3 (Supplementary information, Figure S5C).…”
Section: Nlrc5 Promotes Inflammasome Activationsupporting
confidence: 78%
See 1 more Smart Citation
“…To determine whether NLRC5 is involved in inflammasome activation, NLRC5 or a mutant with the LRR domain deleted, a mutation that is designed to remove the autoinhibitory effect of LRRs, was overexpressed to determine the effect on the processing of procaspase-1 and pro-IL-1β. Overexpressed NLRC5 or its deletion mutant activated this processing, and the mutant also promoted NLRP3 inflammasome activation (Sup- plementary information, Figure S5A), consistent with recent reports [16,17]. Also as reported previously [16], NLRC5 associated with NLRP3 (Supplementary information, Figure S5B), and the NACHT domain of NLRC5 mediated this association with NLRP3 (Supplementary information, Figure S5C).…”
Section: Nlrc5 Promotes Inflammasome Activationsupporting
confidence: 78%
“…Further analyses showed that the nucleotide-binding domain of NLRC5 was critical for its nuclear import and transactivation activity [15]. NLRC5 was also found to contribute to NLRP3 inflammasome activation in vitro [16]. However, one recent in vivo study did not find any role for NLRC5 [17].…”
Section: Introductionmentioning
confidence: 94%
“…Further reports have confirmed the synergy between NLRC5 and NLRP3 in macrophage cells, demonstrating that caspase-1 activity and the subsequent processing of pro-IL-1b and pro-IL-18 in response to NLRP3-specific agonists were inhibited in the absence of NLRC5. Further, self-association of NLRC5 has also been observed to induce inflammasome activation [101].…”
Section: Nlrc5mentioning
confidence: 99%
“…It will be interesting to know how NLRC5 exactly regulates β2M gene expression. As the known mechanism of Protein Cell & (Davis et al, 2011;Yao et al, 2012). We observed that NLRP3 mediated IL-1b production was partially impaired upon NLRC5 deficiency, but Ting's group did not find this phenotype.…”
Section: Roles Of Nlrc5 In Regulating Immune Responses Nlrc5 Is a Masmentioning
confidence: 81%
“…While the role of NLRC5 in regulating MHC class I gene expression is well recognized by intensive studies, previous researches suggested that NLRC5 may also regulate innate immune responses through affecting TLR mediated NF-κB activation, type I interferon (IFN)-producing pathways as well as inflammasome activation (Benko et al, 2010;Cui et al, 2010;Neerincx et al, 2010;Davis et al, 2011;Lamkanfi and Kanneganti, 2012).Two studies showed NLRC5 was a positive regulator of type I IFN producing pathway in human fi broblasts and THP-1 cells (Kuenzel et al, 2010;Neerincx et al, 2010). However, NLRC5 was shown to suppress type I IFN production through association with RIG-I and MDA5 (the dsRNA sensors), or inhibit NF-κB pathway through its direct binding with IκB kinase-α (IKK-α) and IKK-β (Cui et al, 2010).…”
Section: Function Of Nlrc5 In Innate Immune Responsementioning
confidence: 99%